Non-parametric approaches to education and health expenditure efficiency in OECD countries - Afonso, António (2010)
We address the efficiency of expenditure in education and health sectors for a sample of OECD countries by applying two alternative non-parametric methodologies: FDH and DEA. Those are two areas where public expenditure is of great importance so that findings have strong implications in what concerns public sector efficiency. When estimating the efficiency frontier we use both measures of expenditure and quantity inputs. We believe this approach to be advantageous since a country may well be efficient from a technical point of view but appear as inefficient if the inputs it uses are expensive. Efficient outcomes across sectors and analytical methods seem to cluster around a small number of core countries, even if for different reasons: Finland, Japan, Korea and Sweden.